Frequency of Low Bone Mineral Density and Its Age and Gender Related Association in Pakistani Population - Farooq, Muhammad; Shaheen, Sajida; Farooq, Majida; Zafar, Hannan; Saleem, Amna (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the frequency of low bone mineral density and its probable association with age and gender in Pakistani populations in suburban areas of Lahore.Study Design:  Cross-sectional studyPlace and Duration of Study: Combined Military Hospital, Lahore Pakistan, from Feb to May 2018.Methodology: In this study, 249 subjects were selected through non-probability convenience sampling.  Information was endorsed in a pre-designed questionnaire after taking a brief history from all patients. The OsteoSys bone densitometer was used to calculate bone mineral density. To assess bone mineral density and the risk of osteopenia and osteoporosis, T-scores were used. In addition, to maximise accuracy and decrease the chance of error, we calibrated the machine before its use.Results: Osteoporosis was found in 91(36.54%) and osteopenia in 146(58.63%) of participants. Only 12(4.81%) had normal bone mineral density. A significant association of decreased bone mineral density with increasing age was seen (p-value ≤ 0.001).Conclusion: This study revealed a high frequency of low bone mineral density in both genders of the Pakistani suburban population. The frequency increased with advancing age and post-menopausal status.